Virus Detection In Windows 10 Using Nist Method And Smadav Application 13.4: Virus Detection In Windows 10 Using Nist Method And Smadav Application 13.4 - Ahmad Fajar Sidiq; Anton Yudhana; Rusydi Umar (Institute of Computer Science (IOCS), 2020)
This research has a background in virus detection on a computer, because a virus is something that can damage and damage data on a computer, because the impact is very bad for the computer so that many anti-virus viruses develop and continue to be developed each year, the development of the virus first against anti-virus causes the impact of damage that is getting worse, the most severe is data loss, data is very important for a computer, in this study the authors use a method created by the National Institute of Standards and Technology (NIST), with this method will facilitate research carried out, the results of the study will be in the form of detection carried out by the Smadav software version 13.4.